Under the March sun : the story of spring training - Fountain, Charles (Oxford University Press, 2009)
There is nothing in all of American sport quite like baseball's spring training. This annual six-week ritual, whose origins date back nearly a century and a half, fires the hearts and imaginations of fans who flock by the hundreds of thousands to places like Dodgertown to glimpse superstars and living legends in a relaxed moment and watch the drama of journeyman veterans and starry-eyed kids in search of that last spot on the bench. In Under the March Sun, Charles Fountain recounts for the first time the full and fascinating history of spring training and its growth from a shoestring-budget ro.